1987
DOI: 10.1021/ac00136a018
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of .beta.-lactam antibiotics by circular dichroism

Abstract: Circular dichroism spectra have been characterized for nine penicillins and three cephalosporins dissolved In aqueous pH 5.4 buffer solutions. Discriminations among either the penicillin or the cephalosporin homologues are not possible from these spectral data, but the distinction between the two groups Is easy. Direct determinations of penicillin V present In prepared laboratory mixtures with lactose, starch, caffeine, and cephalothln and In pharmaceutical preparations were accomplished after a simple extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…CD, however, has been successfully applied to direct determination of numerous products, including opiates; quinine and quinidine (easily distin- guishable from each other because the Cotton bands are of opposite polarity); reserpine; tetracyclines; penicillins and cephalosporins (whose CD spectra bear no mutual similarities [see Figure 6] in comparison with the absorption spectra); and vitamins (4). Common additives such as aspirin, caffeine, and most simple sugars are noninterfering (4). This list is not especially long, partly because the point clearly has been made that the task of using CD for quality control, without chromatographic separation, is elementary and particularly reliable.…”
Section: Analytical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD, however, has been successfully applied to direct determination of numerous products, including opiates; quinine and quinidine (easily distin- guishable from each other because the Cotton bands are of opposite polarity); reserpine; tetracyclines; penicillins and cephalosporins (whose CD spectra bear no mutual similarities [see Figure 6] in comparison with the absorption spectra); and vitamins (4). Common additives such as aspirin, caffeine, and most simple sugars are noninterfering (4). This list is not especially long, partly because the point clearly has been made that the task of using CD for quality control, without chromatographic separation, is elementary and particularly reliable.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Other equally successful studies have involved assays of hops (humulone) (4); belladonna (atropine) (4); marihuana (THC and CBD) (23); opium (morphine, codeine, thebaine, noscapine) (22); Rauwolfia serpentina (reserpine) (39); fermentation broths (penicillin-V) (40); cattle feed (aureo- (a) Chlortetracycline in 1.0 M in pH 5.6 buffer and (b) aureomycin in pH 5.6 buffer extract of cattlefeed crumbles.…”
Section: Graphics For Chemical Structuresmentioning
confidence: 99%
“…A recent application does describe the use of a combined fluorescence-CD detector in the determination of riboflavin, but only laboratory samples were analyzed (Christensen and Yeung, 1989). We have had a number of recent successes where CD has been used to determine the principal chiroptical analytes in solutions of real pharmaceutical mixtures, e.g., the 0-lactams (Purdie and Swallows, 1987) and cinchona alkaloids (Han and Purdie, 1986), and in extracts of organic materials such as marijuana (Han and Purdie, 1985), opium (Han and Purdie, 1986), and tobacco (Atkinson et al, 1984), penicillin broth (Purdie and Swallows, 1987), and Rauwolfia serpentina (Swallows and Purdie, 1989). Optical activity and absorption are both required for CD activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although these requisites limit the applicability of CD, they also confer to this technique a high degree of analytical selectivity, allowing a CD-active drug to be analyzed directly in a mixture. Thus, recent applications of CD to the pharmaceutical and clinical fields have shown that CD-active drugs can be directly analyzed in their pharmaceutical preparations, additives not interfering with the CD measurement, 4,5 and in urine samples of patients, even when these contain other non-CD-active drugs and/or urinary proteins, it also bring possible to determine the latter simultaneously. 6,7 Blood is the most complex and important of the biological fluids.…”
mentioning
confidence: 99%